Clinical Characteristics of Pediatric Cases of COVID-19 in Hunan, China: A Retrospective, Multi-Center Case Series - Wu, Lei; Zhang, Xiao-Fo; Yang, Yong; Yi, Xiu-Ying; Jiang, Xin-Ping; Han, Hai-Ying; Cao, Xiao-Ying; Wang, Tuan-Mei; Wang, Man-Zhi (Frontiers in Pediatrics, 2021)
Objective: Aimed to investigate the epidemiological characteristics, clinical features, treatment, and short-term prognosis of COVID-19 in children. Methods: Retrospective analysis was conducted in 48 children with COVID-19 admitted to 12 hospitals in eight cities in Hunan province, China, from January 26, 2020 to June 30, 2020. Results: Of the 48 cases, Familial clusters were confirmed for 46 children (96%). 16 (33%) were imported from other provinces. There were 11 (23%) asymptomatic cases. only 2 cases (4%) were severe. The most common symptom was fever (n = 20, 42%). Other symptoms included cough (n = 19, 40%), fatigue (n = 8, 17%), and diarrhea (n = 5, 10%). In the early stage, the total peripheral blood leukocytes count increased in 3(6%) cases and the lymphocytes count decreased in 5 (10%) cases. C-reactive protein and procalcitonin were elevated respectively in 3 (6%) cases and 2 (4%) cases. There were abnormal chest CT changes in 22 (46%) children, including 15 (68%) with patchy ground glass opacity, 5 (22%) with consolidation, and 2 (10%) with mixed shadowing. In addition to supportive treatment, antiviral therapy was received by 41 (85%) children, 11 (23%) patients were treated with antibiotics, and 2 (4%) were treated with methylprednisolone and intravenous immunoglobulin. Compared to 2 weeks follow-up, one child developed low fever and headache during the 4 weeks follow-up, 3 (6%) children had runny noses, one of them got mild cough, and 4 (12%) children had elevated white blood cells and lymphocytes. However, LDH and CK increased at 2 weeks and 4 weeks follow-up. 2 weeks follow-up identified normal chest radiographs in 33 (69%) pediatric patients. RT-PCR detection of SARS-CoV-2 was negative in all follow-up patients at 2 and 4 weeks follow-up. All 48 pediatric patients were visited by calling after 1 year of discharge. Conclusions: Most cases of COVID-19 in children in Hunan province were asymptomatic, mild, or moderate. Close family contact was the main route of infection. It appeared that the younger the patient, the less obvious their symptoms. Epidemiological history, nucleic acid test, and chest imaging were important tools for diagnosis in children.